Managerialism and performativity: is it the only way to quality public school? - Sousa, Mauricio de (Revista Eletrônica de Educação, 2017)
This article presents a research on editorials of the two main printed newspapers with the largest circulation and reach in Brazil: “Folha de São Paulo” and “O Estado de São Paulo”. The editorials were published between 2007 and 2016, and their analysis refer to the relationship between Basic Education Development Index (IDEB) and school management. The concepts of performativity and managerialism developed by Stephen Ball were used to analyze the educational reforms that took place in Europe in the last decades, which have resulted in the introduction of market values and the definition of quality, which is achieved through competition, efficiency, performance and professional accountability. As a consequence of these reforms, we have disqualified public service management, especially in education. Using the analysis of the discourses as a methodology, 30 editorials were studied, and we found that, like in Europe, Brazilian public education is of poor quality, since the students performance in national and international external evaluations is very low. Thus, it is considered that the way to improve the quality of public education would be to reform school management in an efficient and competitive manner. Consequently, the editorials analyzed stated that quality education is what qualifies students for the job market and not for a social transformation, in a perspective of social quality education, valuing the integral formation of the human being. Keywords: Managerialism, Performativity, IDEB, Mass media. References: AFONSO, Almerindo Janela. Questões, objetos e perspectivas em avaliação. Avaliação. São Paulo/Campinas/Sorocaba, v. 19, n. 2. p. 487-507, 2014. ALVES FILHO, Francisco. A autoria institucional nos editoriais de jornais. ALFA: Revista de Linguística, v. 50, n. 1, p. 77-89, 2009. BALL, Stephen J. Education reform: a critical and post-structural approach. Buckingham: Open University Press, 1994. BALL, Stephen J. Diretrizes políticas globais e relações políticas locais em educação. Currículo sem fronteiras, v. 1, n. 2, p. 99-116, 2001. BALL, Stephen J. Performatividade, privatização e o pós-Estado do bem-estar. Educação & Sociedade, v. 25, n. 89, p. 1105-1126, 2004. BALL, Stephen J. Profissionalismo, gerencialismo e performatividade. Cadernos de pesquisa, v. 35, n. 126, p. 539-564, 2005. BALL, Stephen J. Sociologia das políticas educacionais e pesquisa crítico-social: uma revisão pessoal das políticas educacionais e da pesquisa em política educacional. Currículo sem Fronteiras, v. 6, n. 2, p. 10-32, 2006. BALL, Stephen J. Reforma educacional como barbárie social: economismo e o fim da autenticidade. Práxis Educativa, v. 7, n. 1, p. 33-52, 2012. BONAMINO, Alícia; FRANCO, Creso. Avaliação e política educacional: o processo de institucionalização do SAEB. Cadernos de Pesquisa, n. 108, p. 101-132, 2013. BOWE, Richard; BALL, Stephen J.; GOLD, Anne. Reforming education & changing schools: case studies in policy sociology. London: Routledge, 1992. BRASIL. Presidência da república. Casa Civil. Subchefia para Assuntos jurídicos. Decreto nº 6.094, de 24 de abril de 2007. Dispõe sobre a implementação do Plano de Metas Compromisso Todos pela Educação, pela União Federal, em regime de colaboração com Municípios, Distrito Federal e Estados, e a participação das famílias e da comunidade, mediante programas e ações de assistência técnica e financeira, visando a mobilização social pela melhoria da qualidade da educação básica. Disponível em: <http://www.planalto.gov.br/ccivil_03/_ato2007-2010/2007/decreto/d6094.htm>. Acesso em: 30 de março de 2014. FOLHA DE SÃO PAULO. Metas sociais. 30 de setembro de 2010, p. 2. FOLHA DE SÃO PAULO. Educação fora da caixa. 27 de dezembro de 2015, p. 2. FREITAS, Dirce Nei Teixeira. A avaliação da educação básica no Brasil: dimensão normativa, pedagógica e educativa. Campinas: Autores Associados, 2007. GILL, Rosalind. Análise de discurso. In. BAUER, Martin W.; GASKELL, George. Pesquisa qualitativa com texto, imagem e som: um manual prático. Petrópolis, RJ: Vozes, 2008. p. 244-270. IAIES, Gustavo. Evaluar las evaluaciones. In: Unesco. Evaluar las evaluaciones: una mirada política acerca de las evaluaciones de la calidad educativa. Buenos Aires: IIPE; Unesco, 2003. p. 15-36. KLEIN, Ruben. Testes de rendimento escolar. In: MELLO e SOUZA, Alberto (organizador). Dimensões da avaliação educacional. Petrópolis: Vozes, 2005. p.110 -138. MAINARDES, Jefferson. Abordagem do ciclo de políticas: uma contribuição para a análise de políticas educacionais. Educação e Sociedade. Campinas, vol. 27, n. 94, p. 47-69, 2006. MAINARDES, Jefferson. Reinterpretando os ciclos de aprendizagem. São Paulo: Cortez, 2007. MÉZÁROS, István. A educação para além do capital. São Paulo: Boitempo, 2008. MINAYO, Maria Cecília e Souza. O desafio do conhecimento: pesquisa qualitativa em saúde. São Paulo: HUCITEC, 2014. O ESTADO DE SÃO PAULO. Outro triste retrato do ensino. 24 de junho de 2007, p.3. O ESTADO DE SÃO PAULO. Os resultados do IDEB. 13 de junho de 2008, p.3. O ESTADO DE SÃO PAULO. Crime contra as novas gerações. 29 de junho de 2009, p. 3. O ESTADO DE SÃO PAULO. O estado da educação. 16 de agosto de 2012, p. 3. OLIVEIRA, Romualdo Portela de; ARAÚJO, Gilda Cardoso de. Qualidade do ensino: uma nova dimensão da luta pelo direito à educação. Revista Brasileira de Educação. São Paulo, n. 28, p. 5-23, jan./abr. 2005. ORLANDI, Eni P. Análise de discurso: princípios e procedimentos. Campinas: Pontes editora, 2015. REZENDE, Monica; BAPTISTA, Tatiane Wargas Farias. A análise da política proposta por Ball. In: MATTOS, Rubens Araújo; BAPTISTA, Tatiane Wargas Farias. Caminhos para análise das políticas de saúde. Rio de Janeiro: UERJ, p. 173-180, 2011. SHIROMA, Eneida Oto et. al. Decifrar textos para compreender a política: subsídios teórico-metodológicos para análise de documentos. Perspectiva. Florianópolis, v. 23, n. 02, p. 427-446, julho/dezembro 2005. SILVA, Lidiane Rodrigues Câmpelo et al. Pesquisa documental: alternativa investigativa na formação docente. In: Anais do IX CONGRESSO NACIONAL DE EDUCAÇÃO (EDUCERE) E III ENCONTRO SUL BRASILEIRO DE PSICOPEDAGOGIA. Paraná: outubro de 2009. p. 4554 a 4566. Disponível em: file:///C:/Users/USER/Documents/unicamp%20-%20Doutorado/texto%20medologia%20documetal.pdf. Acesso 30 de novembro 2014. SILVA, Maria Abadia. Qualidade social da educação pública: algumas aproximações. Cadernos Cedes. Campinas. Vol. 29, n. 78, p. 216-226, maio/agosto 2009. VIANNA, Heraldo Marelim. Fundamentos de um programa de avaliação educacional. Meta: Avaliação, Rio de Janeiro, v.1, n.1, p. 11-27, jan/abril 2009.